Influenza risks arising from mixed intensive pig and poultry farms, with a spotlight on the United Kingdom - Mace, Jenny L.; Knight, Andrew (Frontiers in Veterinary Science, 2023)
Diseases passed to humans from animals (zoonoses) constitute 73% of emerging infectious diseases.Farmed animals are considered a high zoonotic risk, especially poultry and pigs as evidenced by recent outbreaks of avian and swine influenza. This review sought to collate recent knowledge of the disease risks from keeping pigs and chickens intensively and in close proximity to each other. Recent knowledge on influenza viruses compounds the public health concerns; no longer are concerns about 'mixing vessel' hosts limited to pigs, but several other animal species too at a high level of probabilitymost notably chickens and humans. More generally, scientific literature establishing positive associations between intensive animal farming, human population growth, reduced 2 This is a provisional file, not the final typeset article biodiversity, and increased zoonoses risks is abundant. This includes the publication of relevant systematic reviews. The collected scientific evidence on this issue is clear: there is exceptionally strong evidence for a link between low animal welfare levels and high zoonotic risks, exacerbated by animal crowding, low genetic diversity, compromised hygiene, and high animal stress levels which compromise immune systems. Based on this evidence, further industrialised animal farmsespecially poultry and pig farms or a mix thereof, and particularly in areas that already have a high concentration of farmed animalsshould not generally be permitted to proceed. Instead, efforts should concentrate on supporting arable agriculture (or transitions towards this) and de-intensifying remaining animal farms, in alignment with One Health/One Welfare approaches within which animal health and welfare are integral parts of any farming operation. Amongst numerous other factors, this would involve reducing stocking densities down to 11kg/m 2 (around five chickens/m 2 ) for meat chickens, and down to one pig/1.5m 2 for pigs (assuming a 100kg pig).